Mechanistic Characteristics of HRS-WC Mixture Using Tabas Stone Waste Coated With Plastic Waste As Aggregate - Ariawan, I Made Agus; Wedagama, Dewa Made Priyantha; Elizar; Genta Putra, Komang Alit; I Putu Chandra Wibawa (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Utilization of tabas stone waste and polypropylene (PP) plastic waste has not been carried out massively and optimally because it lacks economic value. The Tabas stone waste can be used as an aggregate for pavement. The porous characteristic of tabas stone results in a high rate of absorption and abrasion, so modifications are made by coating the aggregate with an PP plastic. The aim of this experiment was to determine the characteristics of the HRS-WC mixture with the aggregate of tabas stone coated with plastic. The initial step of this research was testing the tabas stone aggregates, bitumen material, and PP plastic according to the SNI procedure, the next step was Marshall test to find the Optimum Bitumen Content (OBC), the OBC value was obtained by 10%. Coating the aggregate with shredded plastic measuring ± 1 cm2 was done on coarse aggregate only using the dry method with the proportions of plastic are 5% and 10% of the total weight of coarse aggregate. The characteristics of the aggregate coated with plastic decrease in the value of absorption and abrasion, but only 10% of the plastic content met the specifications with a value of 2.5% and 19.63%. The Marshall testing on the HRS-WC mixture with plastic-coated aggregates was done at variations in bitumen content of 8.5%; 9%; 9.5%. The mixture at 5% plastic content only 9.5% bitumen content met the specifications, namely: stability 1352.72 kg, flow 3.39 mm, MQ 402.23 kg/mm, VIM 5.75%, VMA 18.62% , and VFB 69.16%. When at 10% plastic content, only 9% and 9.5% bitumen content met the specifications, namely the stability of 1370.06 kg; 1456.21 kg, flow 3.81 mm; 3.98 mm, MQ 365.31 kg/mm; 370.06 kg/mm, VIM 5.77%; 4.89%, VMA 18.07%; 18; 15%, and VFB 68.05%; 73.04%. Asphalt mixture of 9% bitumen content, 10% plastic content has more ITSM  value compared to 5% plastic content. This is due to the plastic content in the mixture of 10% plastic content which causes the mixture to be stiffness. Asphalt mixture with a plastic content of 5%, with an bitumen content of 9.5% faster than the mixture with an bitumen content of 8.5% and 9% in the ITFT test. Asphalt mixture with a plastic content of 5%, with a variation of bitumen of 8.5% experienced a decrease in the dynamic creep strain value until the bitumen content was 9.5%. A mixture with a plastic content of 5% aggregate coating is recommended for HRS WC that uses tabas stone.